Brand matters: an examination of small-to-medium sized enterprises - Napoli, Julie; Ewing, M.; Berthon, P. (Australian and New Zealand Marketing Academy, 2005)
While an impressive body of literature has emerged focusing on the critical activities involved in brand management for larger organizations, no research has been undertaken to examine branding within small to medium sized enterprises (SMEs). The present study therefore examines the nature and scope of brand management within an SME context. Findings show significant differences between small and large organizations along nine of the ten brand management dimensions reported in Keller’s (2000) brand report card. Moreover, different brand management practices are associated with business performance in SMEs. Implications of the study are highlighted, limitations noted and directions for future research outlined.